(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Teacher professional development is a line of research in science teaching processes. Teacher training processes include the analysis of the components of pedagogical content knowledge. This paper socializes a process of intervention of a teacher development program in a case study with two chemistry teachers of the municipality of Talca (Chile). It was carried out from a qualitative framework with a descriptive approach. It is identified in the teachers that the student’s knowledge of science is the category where the relationships of the components of the pedagogical knowledge of the content converge, in which the student’s difficulties regarding the following of instructions and the contrast between the theoretical and experimental work are the most identified components, in addition to managing the self-evaluation of the practical work in the classroom process.